Tuina for cervical vertigo: A systematic review and meta-analysis of randomized controlled trials. (May 2020) - Huang, Fan; Zhao, Siyi; Dai, Lin; Feng, Zitong; Wu, Zhennan; Chen, Jia; Guo, Rusong; Tian, Qiang; Fan, Zhiyong; Wu, Shan
Abstract: Background and purpose: Cervical vertigo (CV), one of the most common causes of vertigo, makes patients feel dizzy, which seriously affects patients' lives. As a traditional Chinese bone-setting manipulation, Tuina is widely used to treat CV. This article aims to evaluate the effectiveness and safety of Tuina for CV. Methods: Nine databases were searched. Methodological quality was evaluated with the Cochrane Collaboration's tool. Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was applied to determine confidence in the effect estimates. Stata 12.0 software was used to carry out the meta-analysis, and a trial sequential analysis (TSA) was performed with TSA 0.9. Results: Nine randomized controlled trials (RCTs) were included. Low-quality evidence suggested that Tuina showed a significantly higher effectiveness rate compared to massage therapy (risk ratio (RR) = 1.11, 95% confidence intervals (CI): 1.05 to 1.17, p < 0.0001) and cervical traction (RR = 1.37, 95% CI: 1.09 to 1.72, p = 0.007; I 2 = 0%, p = 0.826). Two trials reported that Tuina was better than acupuncture (RR = 1.40, 95% CI: 1.07 to 1.83) or betahistine mesilate (RR = 1.17, 95% CI: 0.99 to 1.37) based on an improved effectiveness rate. Low-quality evidence showed that Tuina was superior to massage therapy in improving scores on the evaluation scale for cervical vertigo (ESCV) (weighted mean differences (WMD) = 2.52, 95% CI: 1.11 to 3.94, p < 0.0001). Adverse events were tolerable. TSA revealed that an improved effectiveness rate was indicated. Conclusion: Tuina might improve the effectiveness rate and ESCV scores in patients with CV. However, the level of all the available evidence was low, and larger-scale and well-designed RCTs should be encouraged.